2017
DOI: 10.1080/10641963.2017.1324474
|View full text |Cite
|
Sign up to set email alerts
|

Non-dipping status and selected adipokines concentration in children with primary arterial hypertension

Abstract: The concentration of leptin and apelin in HT-OB children was significantly higher than in the C and HT-NW group. A similar finding for leptin level was demonstrated in comparison of HT-NW with C group. In children with HT-OB, the lack of decline in nocturnal DBP was associated with significantly higher BMI and the Cole's Index value. Children with HT-OB and lack of decline in nocturnal SBP showed lower leptin and insulin concentrations, and lower values of HOMA-IR as compared with dipping children. Positive co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 26 publications
1
5
1
1
Order By: Relevance
“…In the group of children and adolescents with normalweight hypertension, the correlation between ghrelin, leptin and adiponectin and anthropometrical parameters has also been found. In a recent study, leptin was shown to correlate with blood pressure, but this was not confirmed in our study [32]. However, ghrelin and adiponectin have been confirmed as cardiovascular markers in normal-weight hypertensive patients, which has not been proven in children until now, although this correlation has been found in adult patients [36].…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…In the group of children and adolescents with normalweight hypertension, the correlation between ghrelin, leptin and adiponectin and anthropometrical parameters has also been found. In a recent study, leptin was shown to correlate with blood pressure, but this was not confirmed in our study [32]. However, ghrelin and adiponectin have been confirmed as cardiovascular markers in normal-weight hypertensive patients, which has not been proven in children until now, although this correlation has been found in adult patients [36].…”
Section: Discussioncontrasting
confidence: 91%
“…In the present study, their observed correlation with systolic blood pressure indicates their role in hypertension risk. Recently, leptin has been found to play a role in obesity-related hypertension [32,33] as has adiponectin in adult men [34].…”
Section: Discussionmentioning
confidence: 99%
“…Varda et al observed in infants and toddlers from 2 to 30 months old a less pronounced night dip of only 5.4% on average [42]. A recent study observed a close relationship between non-dippers and BMI with children with primary hypertension and overweight or obesity showing a lack of decline of nocturnal blood pressure values [43]. Unfortunately, that study lacks information on GA or birth weight.…”
Section: Discussionmentioning
confidence: 99%
“…Strengths of this study are the availability of comprehensive perinatal, neonatal, maternal, infant, and early childhood data; serial anthropometric data; and comprehensive assessment including BP at 6 to 7 years of age. Limitations include the lack of a term control population; no data on maternal prepregnancy weight, weight gain in pregnancy, dietary intake, renal findings, or BP at earlier ages 55,56 ; those lost to follow-up had higher rates of public insurance, cesarean delivery, and bronchopulmonary dysplasia, creating a possible bias; and a single visit with duplicate measurements of BP.…”
Section: Discussionmentioning
confidence: 99%